STUDIES ON THE OPTIMIIZATION OF BIOMASS PRODUCTION USING KLUYVEROMYCES MARXIANUS ISOLATED FROM PANEER WHEY - MEERA BABU; SHANTHA PREMA RAJ; NIRMALA C. B; DECCARAMAN M (International Journal of Pharma and Bio Sciences, 2014)
In the present study Kluyveromyces marxianus isolated from paneer whey was employed for biomass production. Various parameters like pH, temperature and nitrogen source were optimized for maximum biomass yield. The biomass yield was studied to vary with different nitrogen sources, pH and temperature. Ammonium sulphate, ammonium nitrate, beef extract and yeast extract were used as nitrogen sources. In addition, the concentration of the nitrogen source at which the biomass yield proved to be high was also optimized. Among the nitrogen sources tested, ammonium sulphate showed maximum yield at a concentration of 0.4mg/ml. The results of the study conclude that Kluyveromyces marxianus could be effectively produced from paneer whey at optimal conditions and used for various industrial applications.